Study on the Bending Fatigue Behavior of Single Aramid Fibers by a Novel Bending Fatigue Test Method (Journal of Fiber Bioengineering and Informatics, 2014)
In this paper, we report a bending fatigue testing apparatus which can test the bending fatigue resistanceof single Kevlar 49 fiber by setting the pretension and bending angle. The cyclic tension and the (numberof cyclic bending of fiber) were recorded by this apparatus. The cyclic tension curve showed that thetension changes in periods during the bending fatigue process. The cyclic tension was theoreticallyanalyzed and found that the bending angle had significant effect on the cyclic tension. The cyclicbending number N of Kevlar 49 fiber was plotted as a function of pretension S using S-N curves, whichshows that the bending angle and pretension have a significant effect on the fatigue lifetime of a fiber.The bending fatigue morphologies of Kevlar 49 fiber explained the bending failure mechanism of theKevlar 49 fibers.